2009
DOI: 10.1159/000214218
|View full text |Cite
|
Sign up to set email alerts
|

Use of Doppler Ultrasound to Assess Femoral Artery Adaptations in the Hemiparetic Limb in People with Stroke

Abstract: Background: A reduction in physical activity combined with decreased demand for leg oxygen consumption may affect blood flow to the hemiparetic lower extremity after stroke. The purpose of this study was to characterize femoral artery adaptations that occur in the hemiparetic leg in chronic stroke. A secondary goal was to examine intrarater reliability using Doppler ultrasound in people with hemiparesis after stroke. Methods: This descriptive study used a sample of convenience at 2 locations (urban medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…(9) In 2004, Ivey et al used strain gauge plethysmography to examine vascular endothelial function in the lower limbs in people with chronic stroke. (5) They reported findings similar to our previous work(6, 7) regarding between limb differences. Ivey and colleagues explored whether these alterations were a function of reduced lean muscle mass using dual energy X-ray absorptiometry.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…(9) In 2004, Ivey et al used strain gauge plethysmography to examine vascular endothelial function in the lower limbs in people with chronic stroke. (5) They reported findings similar to our previous work(6, 7) regarding between limb differences. Ivey and colleagues explored whether these alterations were a function of reduced lean muscle mass using dual energy X-ray absorptiometry.…”
Section: Discussionsupporting
confidence: 88%
“…Although we have observed unilateral changes resting blood flow and arterial diameter in the femoral artery of the hemiparetic leg in chronic stroke,(6, 7) it is unclear when these changes occur or the mechanisms involved. Vascular endothelial function via FMD in the brachial artery has been reported to be reduced in chronic(3) stroke when compared to controls.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Many studies on stroke patients showed that the lower leg blood flow in the affected limb decreased during rest and exercise [25,26,27], and the blood flow in the femoral artery of the hemiparetic limb was significantly lower at rest when compared to the other limb [27]. Other studies have also reported that the structural vascular remodeling, characterized by a decreased diameter of vessel and blood flow in the femoral artery of the paralyzed side, may occur after stroke [26,28]. The literature suggests that impaired motor function and lower activity level after stroke reduce the needs for blood flow and muscular metabolic activity in the hemiparetic leg [25].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced exercise capacity is also supported to result from unilateral dysfunction of the paretic limb [7][8][9][10]. Adaptations that have been reported are reduction of femoral artery diameter [8,9], blood flow reduction [7,9,10], change in tissue composition [11][12][13], and vasomotor reactivity [9,10].…”
Section: Introductionmentioning
confidence: 94%